2018
DOI: 10.1002/cam4.1668
|View full text |Cite
|
Sign up to set email alerts
|

Incidence proportions and prognosis of breast cancer patients with bone metastases at initial diagnosis

Abstract: IntroductionPopulation‐based data on the incidence and prognosis of bone metastases at diagnosis of breast cancer are currently limited. Hence, we conducted this study to analyze the incidence proportions and prognostic factors of patients with breast cancer and bone metastases at the time of cancer diagnosis.Materials and methodsPatients with primary invasive breast cancer and bone metastases at initial diagnosis between 2010 and 2014 were identified using the Surveillance, Epidemiology, and End Results (SEER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 40 publications
11
40
0
1
Order By: Relevance
“…HR+/HER2-breast cancer were historically considered to have a relatively favorable prognosis, whereas HR+/HER2+ subtype seemed to have the best prognosis and HR+/HER2-and HR-/HER2+ subtype had similar survival among patients with de novo metastatic breast cancer in the HER2-targeted therapy era [49,50]. Among breast cancer patients with de novo brain or bone metastases, results were consistent with those in de novo metastatic breast cancer patients [51,52], while HR-/HER2+ subtype had a worse prognosis than the HR+/HER2-subtype among breast cancer patients with de novo lung metastases [53]. Differently, HR-/HER2+ BCLM patients may have a better prognosis than the HR+/HER2-subtype in our study.…”
Section: Discussionsupporting
confidence: 56%
“…HR+/HER2-breast cancer were historically considered to have a relatively favorable prognosis, whereas HR+/HER2+ subtype seemed to have the best prognosis and HR+/HER2-and HR-/HER2+ subtype had similar survival among patients with de novo metastatic breast cancer in the HER2-targeted therapy era [49,50]. Among breast cancer patients with de novo brain or bone metastases, results were consistent with those in de novo metastatic breast cancer patients [51,52], while HR-/HER2+ subtype had a worse prognosis than the HR+/HER2-subtype among breast cancer patients with de novo lung metastases [53]. Differently, HR-/HER2+ BCLM patients may have a better prognosis than the HR+/HER2-subtype in our study.…”
Section: Discussionsupporting
confidence: 56%
“…Chen et al reported that in axillary lymph node metastasis, CA125, CA153, ALP, and hemoglobin concentration were independent risk factors for BM in BC patients [ 22 ]. Yue Gong et al determined that age, ethnicity, histology, grade, tumor subtype, extra bone metastasis site, and education level were predictors of BM in BC patients [ 23 ]. Other studies have also reported that involvement of more than four axillary lymph nodes at initial diagnosis, primary tumor size greater than 2 cm, estrogen receptor positive and progesterone receptor negative tumors and younger age are risk factors for BM in BC patients [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that patients with only BM develop vital organ dysfunction later, so these patients have a higher survival rate than those with both bone and extraosseous metastases. According to previous research, the breast cancer subtype is an independent risk factor for the occurrence of metastasis, and the incidence of BM is highest in BC patients that are HR+/HER2− or HR+/HER2+ [ 23 , 32 ]. Our results show that patients with HR+/HER2- BC have a higher risk of BM, and patients with Grade 2 BC are more likely to have BM compared to patients with Grades 3 and 4 BC, which is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of bone metastases in lung cancer reported by Gustavo et al and Katrin et al depended on the histological subtype [22,23]. For breast cancer, it has been demonstrated that patient age, hormone receptor status, human epidermal growth factor receptor 2 and tumor size contribute to bone metastases [28,29]. Ruatta et al reviewed and analyzed renal cancer patients in their clinics and found that approximately 4% of patients had bone metastases at the time of initial diagnosis, while approximately 13% of patients had metastases during follow-up [30].…”
Section: Discussionmentioning
confidence: 99%